Some aspects of using the nanotechnology in food industry - Fursik, Oksana; Strashynskyi, Igor; Pasichnyi, Vasyl; Marynin, Andriy (My University, 2019)
The article presents data from a literature review of the modern areas of nanotechnology application in food industry, their properties, interaction with biopolymers in food products.At present, nanosized SiO2 is one of the most common nanoadditives in various branches of the food industry. Scientific studies show that silica, due to its structural features and large surface area, has high adsorption properties with respect to water, proteins, exo- and endotoxins, and pathogenic microorganisms.Numerous studies confirm the possibility of effective modification of the gum’s rheological characteristics during their joint use with silica as a part of functional-technological compositions.It was established by an experimental method that the addition of SiO2 to the hydrated soy proteins and protein preparations containing collagen led to a densification of the mixture, modifying their rheological and functional properties.Conducted scientific studies of the use of nanocomposites in the technology of meat-containing culinary semi-finished products confirm the effectiveness of the use of finely divided silica as a texture-forming additive.After analyzing the scientific research of domestic and foreign scientists, it can be argued that nanoparticles directly affect the absorption and assimilation of nutrients due to physico-chemical modifications that occur during the interaction of food components with nanoparticles.
Keywords: nanotechnology; application; properties; dioxide silica; food products; gums; meat products; нанотехнології; застосування; властивості; діоксид кремнію; харчові продукти; камеді; м’ясні вироби; синергізм; кафедра технології м’яса і м’ясних продуктів; кафедра технологічного обладнання та комп’ютерних технологій проектування